1984
DOI: 10.1002/ajh.2830160206
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in sickle cell anemia

Abstract: A review of the electrocardiograms (ECG) of 108 patients with sickle cell anemia found only 3 with patterns consistent with myocardial infarction. Two of the 3 patients with ECG infarct patterns had postmortem examination confirmation of the infarction. These two patients had no significant coronary atherosclerosis nor did the other six autopsied patients in the present series. Literature reports of postmortem examinations on patients with sickle cell anemia confirm the scarcity of coronary atherosclerosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…Amitriptyline and other tricyclic antidepressants have been shown to reduce acid SMase activity and exosome formation. 35,36,49 Amitriptyline significantly reduced MP generation from SS RBCs in vitro ( Figure 7A-C). Hypoxia has been shown to enhance MP generation 28 and we confirmed that in nonsickle mice with normal functioning spleens, MP production was significantly elevated after 24 hours hypoxia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Amitriptyline and other tricyclic antidepressants have been shown to reduce acid SMase activity and exosome formation. 35,36,49 Amitriptyline significantly reduced MP generation from SS RBCs in vitro ( Figure 7A-C). Hypoxia has been shown to enhance MP generation 28 and we confirmed that in nonsickle mice with normal functioning spleens, MP production was significantly elevated after 24 hours hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…33,34 Becker et al discovered that ceramide production in the lungs contributed to inflammatory cytokine production during cystic fibrosis, 35 and amitriptyline reduced ceramide production, inflammatory cytokine production, and inflammatory cell recruitment in a mouse model of cystic fibrosis. 35,36 Other studies have shown that SMase-mediated ceramide synthesis in plasma membranes promotes microvessel formation. 9,37 We found that the ceramide:SM ratio in SS RBCs and MPs was increased, which corroborates the finding that acid SMase is activated in SS RBCs ( Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…In aggregate, these data suggest that circulating mononuclear cells participate in a compensatory response to the repetitive vascular injury characteristic of sickle cell disease. 43,44,63,64 For example, despite having reduced nitric oxide bioavailability and endothelial dysfunction, 27,28 patients with sickle cell disease do not develop atherosclerotic coronary disease, [65][66][67] which may be due to the vascular protective functions of the HO-1 and p21 systems. Other antioxidant genes such as glutathione peroxidase, thioredoxin, and thioredoxin peroxidase are up-regulated in sickle cell patients, demonstrating a compensatory response to chronic ischemiareperfusion-induced oxidant injury.…”
mentioning
confidence: 99%
“…Literature reports of postmortem examinations on SCA patients confirmed the scarcity of coronary artherosclerosis and myocardial infarction. 10 Defective lipid in sickle cell anaemia has been attributed to increased cholesterol utilization consequent to increased erythropoiesis as there is ongoing haemolysis as well as compensation by bone marrow 4 , however the pathogenesis is yet to be fully elucidated. Abnormal long chain polyunsaturated (N-6 and N-3) fatty acid composition in the red cells has been found to be more remarkable in SCA than other sickle cell disorders.…”
Section: Introductionmentioning
confidence: 99%